The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1097/00004032-199005000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of 239Pu in Soil and Plants in the Nishiyama District of Nagasaki

Abstract: Nishiyama district in Nagasaki is located approximately 3000 m east of the hypocenter of the atomic bomb that was dropped on 9 August 1945. This district is also known as an area where there was a concentrated radioactive fallout with the black rain that was carried by a westerly wind. The Nagasaki atomic bomb was a Pu bomb, and the fallout must have included 239Pu without fission in addition to fission products. The presence of 239Pu in Nishiyama district has been confirmed previously. In this study, the dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…The highest 239þ240 Pu activity concentration in surface 0e5 cm, 59.9 AE 0.81 Bq/kg (dry weight), was observed at N1 on the slope 300 m west from the Nishiyama reservoir (2.4 km east from the hypocenter). This value is comparable with the values reported before (Mahara and Miyahara, 1984;Okajima et al, 1990). The concentration decreased sharply with increasing distance from the Nishiyama reservoir, and reached the same range as global fallout Pu in surface soil of Japanese forests, 0.15e4.31 Bq/kg (dry weight) (Muramatsu et al, 2003).…”
Section: Pu Isotopes In Soilssupporting
confidence: 89%
See 2 more Smart Citations
“…The highest 239þ240 Pu activity concentration in surface 0e5 cm, 59.9 AE 0.81 Bq/kg (dry weight), was observed at N1 on the slope 300 m west from the Nishiyama reservoir (2.4 km east from the hypocenter). This value is comparable with the values reported before (Mahara and Miyahara, 1984;Okajima et al, 1990). The concentration decreased sharply with increasing distance from the Nishiyama reservoir, and reached the same range as global fallout Pu in surface soil of Japanese forests, 0.15e4.31 Bq/kg (dry weight) (Muramatsu et al, 2003).…”
Section: Pu Isotopes In Soilssupporting
confidence: 89%
“…1b and c. As reported in previous papers (e.g. Yamamoto et al, 1983Yamamoto et al, , 1985Okajima et al, 1990;Kudo et al, 1991), high concentrations of Pu isotopes in soils around the Nishiyama reservoir were observed. The highest 239þ240 Pu activity concentration in surface 0e5 cm, 59.9 AE 0.81 Bq/kg (dry weight), was observed at N1 on the slope 300 m west from the Nishiyama reservoir (2.4 km east from the hypocenter).…”
Section: Pu Isotopes In Soilssupporting
confidence: 81%
See 1 more Smart Citation
“…The half-life of cesium-137 is relatively short (30.1y), nevertheless it is still possible to use this radionuclide for identification of source of the contamination. The main source of this isotope in the environment were the Chernobyl accident and nuclear weapon testing [17]- [20]. The 239,240 Pu/ 137 Cs activity ratio of 0.018 and 238 Pu/ 137 Cs activity ratio of 0.00068 the representative value of global fallout in soil were determined by Bunzl and Kracke in 1988 [21].…”
Section: Introductionmentioning
confidence: 99%
“…A review article entitled "Plutonium in the Environment" (Harley6» stimulated studies for Nagasaki. Yamamoto et al7> and Okajima et al 8 ) measured plutonium concentrations in environmental samples around the city of Nagasaki and found that there were some elevated levels of 239+24~and 137CS. They were, however, not able to recognize the degree of scientific importance of the radioactive residues from the first Pu A-bomb explosion with a human loss.…”
Section: Introduction a Nagasaki A-bomb And Sciencementioning
confidence: 99%